Surgical technique for treating bilateral assymetric cleft lip - Rossell Perry, Percy (2012)
Introduction: The anatomy of bilateral cleft lip is different for each patient, and many authors have described modifications of the traditional repairing techniques in order to achieve more individualized designs and better results. The techniques described by Millard and Mulliken are probably the most commonly used all over the world for repairing bilateral cleft lip; however, there are some short-comings when trying to repair asymmetric forms of bilateral cleft lip. So, we designed this technique aiming to correct asymmetry in bilateral cleft lip. This technique is based on a double advancement and lateral rotation concept placing the scars over the natural lines between the esthetic subunits of the upper lip. Matherial and Methods: This is a retrospective and descriptive study based on a case series. We present a new technique used for surgical repair of bilateral cleft lip in 125 patients. The technique is based in the double advancement and lateral rotation concept which allows lengthening of the shortest lateral lip segment. Most of the incisions are performed on the natural lip landmarks, between the aesthetic subunits of the upper lip. Results were assessed considering the number of failures observed after following up patients for more than one year, performing physical examination and analyzing standardized postoperative pictures. Results: This technique has been used in 125 procedures for repairing cleft lip. We obtained good functional and esthetic outcomes for both nose and lips using this technique. The rate of poor results was 15/125 (12%). These latter procedures had to undergo major secondary surgical revisions. Conclusions: We describe a new technique for surgical repair of asymmetric bilateral cleft lip. This technique led to the elongation of the shortest lateral labial segment, allowing us to achieve good esthetic and functional results on upper lip and nose reconstruction in cases of bilateral asymmetric cleft lip.